Design and analysis of chassis and steering system for battery electric vehicle (nanyang venture 10) - Xu, Weijie (2018)
This Final Year Project Report (FYP) is an initiative by Nanyang Technological University (NTU) to research and develop battery electric vehicles (BEV) for competing in Shell Eco Marathon in efforts to create energy efficient vehicles. Nanyang Venture 10 (NV10) is the tenth car in the Nanyang Venture series and competed in its debut competition, Shell Eco Marathon 2018, under the Urban Concept grouping. Leveraging on the design of Nanyang Venture 8, improvements were made to reduce the weight of the vehicle as well as improving its ergonomics. This report focuses on the tasks assigned to the author, which includes the design, analysis and fabrication of the chassis and steering system of NV10 as well as the supplementary tasks. Weight saving was the main design objective as weight plays a major role in the overall efficiency of the vehicle. A lighter vehicle would improve the efficiency as it reduces the load on the rear-wheel mounted in-hub motors. Simulation results are included in this report to verify the design effectiveness in various scenarios.